2021
DOI: 10.3390/app11156940
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of GA Parameters for Layout Design Optimization Problems Using Design of Experiments

Abstract: In manufacturing-cell-formation research, a major concern is to make groups of machines into machine cells and parts into part families. Extensive work has been carried out in this area using various models and techniques. Regarding these ideas, in this paper, experiments with varying parameters of the popular metaheuristic algorithm known as the genetic algorithm have been carried out with a bi-criteria objective function: the minimization of intercell moves and cell load variation. The probability of crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The proposed approach shows promise in optimizing CF and layout design problems. Modrak et al [ 32 ] used the Taguchi method to determine the best configuration of parameters that affect the performance of GA in layout design and CF problems. They investigated the impact of noise variables, including balance weight factor, probability of mutation, and probability of crossover, on the optimal combination of genetic operators.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed approach shows promise in optimizing CF and layout design problems. Modrak et al [ 32 ] used the Taguchi method to determine the best configuration of parameters that affect the performance of GA in layout design and CF problems. They investigated the impact of noise variables, including balance weight factor, probability of mutation, and probability of crossover, on the optimal combination of genetic operators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The underlying concept of GA is based on the principles of natural selection and genetics, which were initially proposed by Holland [37]. The following sequence of steps for GA can be applied to the setting of part-machine CF [32,33].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…The test results demonstrated that the proposed strategy outperformed the competing algorithms. The primary objective of Modrak et al [31] was to discover how to solve the issues of Cell Formation and layout design. Changes to the GA parameter set resulting from research have an effect on the CMS issue.…”
Section: Ga and Hybrid Ga Approaches To Solve Cell Formation And Mach...mentioning
confidence: 99%
“…Modrak, Pandian, and Semanco [56] focussed on finding out how the solutions of the cell formation and layout design problem of CMs are affected by changing the set of GA parameters. On this basis, they used Takuji's approach to find the optimum combination of GA parameters that can improve its efficiency, and explore whether this optimum combination can be affected by noise factors, which are represented by the size of the matrix in that research.…”
Section: Ga To Solve Cell Machine Layout Problemsmentioning
confidence: 99%